Impact of aquaculture training on farmers’ income: Cluster randomized controlled trial evidence in Ghana - Ragasa, Catherine; Amewu, Sena; Agyakwah, Seth K.; Mensah, Emmanuel; Asmah, Ruby (Wiley, 2022)
Aquaculture in Ghana is experiencing tremendous growth, led mainly by large-scale commercial cage operators. A major objective of the government and its partners is to ensure that this rapid growth is sustainable and includes small-scale farmers and poor rural producers. This paper evaluates the aquaculture trainings implemented in six main tilapia-producing regions in Ghana as part of the Ghana Tilapia Seed Project. The impact evaluation is designed as a cluster randomized controlled trial, with half of the producing districts randomly-assigned as the treatment and the rest as the control, complemented by qualitative interviews. One year after the trainings, results show positive impacts on the adoption of good record-keeping, water management, and some biosecurity practices, and on productivity and incomes. In terms of mechanism, improved management practices resulted from reducing overstocking, reducing inbreeding, maintaining water level for fish ponds, regular pond clearing and establishing physical barriers, following advice and recommendations on feeding practices, and complementing feeding practices with farmers’ own feed formulation. Half of the trained farmers experienced lower fish mortality, faster growth, and heavier fish at harvest. Marketing and processing advice through the trainings and complementary FishConnect WhatsApp platform likely contributed to higher incomes, although the platform's coverage and regular updating can be improved.